Ovarian Cancer-Driven Mesothelial-to-Mesenchymal Transition is Triggered by the Endothelin-1/β-arr1 Axis - Del Rio, Danila; Masi, Ilenia; Caprara, Valentina; Spadaro, Francesca; Ottavi, Flavia; Strippoli, Raffaele; Sandoval, Pilar; López-Cabrera, Manuel; Sainz de la Cuesta, Ricardo; Bagnato, Anna; Rosanò, Laura (Frontiers in Cell and Developmental Biology, 2021)
Transcoelomic spread of serous ovarian cancer (SOC) results from the cooperative interactions between cancer and host components. Tumor-derived factors might allow the conversion of mesothelial cells (MCs) into tumor-associated MCs, providing a favorable environment for SOC cell dissemination. However, factors and molecular mechanisms involved in this process are largely unexplored. Here we investigated the tumor-related endothelin-1 (ET-1) as an inducer of changes in MCs supporting SOC progression. Here, we report a significant production of ET-1 from MCs associated with the expression of its cognate receptors, ETA and ETB, along with the protein β-arrestin1. ET-1 triggers MC proliferation via β-arrestin1-dependent MAPK and NF-kB pathways and increases the release of cancer-related factors. The ETA/ETB receptor activation supports the genetic reprogramming of mesothelial-to-mesenchymal transition (MMT), with upregulation of mesenchymal markers, as fibronectin, α-SMA, N-cadherin and vimentin, NF-kB-dependent Snail transcriptional activity and downregulation of E-cadherin and ZO-1, allowing to enhanced MC migration and invasion, and SOC transmesothelial migration. These effects are impaired by either blockade of ETAR and ETBR or by β-arrestin1 silencing. Notably, in peritoneal metastases both ETAR and ETBR are co-expressed with MMT markers compared to normal control peritoneum. Collectively, our report shows that the ET-1 axis may contribute to the early stage of SOC progression by modulating MC pro-metastatic behaviour via MMT.